IMPLEMENTASI FATWA DEWAN SYARIAH NASIONAL NOMOR. 03/DSN-MUI/IV/2000 TENTANG DEPOSITO (STUDI PADA BANK MUAMALAT INDONESIA CABANG PALU) - Soimun Rohman; Ermawati; Murniati Ruslan (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
Sharia banks in conducting business activities must be based on sharia principles. Based on the mandate of Law Number. 21 of 2008 concerning Islamic Banking and BI Regulation Number. 6/24 / PBI / 2004 that the DSN has the duty and authority to stipulate fatwas regarding products and services in the business activities of Banks which carry out business activities based on Sharia principles. To ensure that the deposit products at Bank Muamalat comply with the standards set by the DSN, a research was conducted at Bank Muamalat Indonesia, the Palu branch. Deposit products at the Palu branch of Bank Muamalat Indonesia use the Mudharabah Mutlaqah contract, where BMIs are given freedom in managing customer funds. Then it is reviewed on the rules of the DSN-MUI Fatwa Number. 03 / DSN-MUI / IV / 2000 based on the 6-point provision that must be implemented to achieve sharia principles. In its implementation, the mudharabah time deposit product run by Bank Muamalat Indonesia, Palu branch has met these provisions. so theproduct of mudharabah time deposits or deposits in the Palu branch of Bank Muamalat Indonesia is in accordance with the fatwa.